Micro-Organisms Isolated from Open Fractures of Extremities - Zaman, Ronaq; Deeba, Farah; Roghani, Arsalan Shah; Roghani, Faizan Shah; Inam, Mohammad (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine the frequency of micro-organisms from culture reports of open fractures of extremities. METHODOLOGY: In this descriptive cross-sectional study carried out in the orthopedic surgery department of Lady Reading Hospital in Peshawar, 173 patients with open fractures lasting more than five days were included. The trial lasted for six months. Consecutive non-probability sampling was used. Swabs were collected from the fracture wounds. Swabs were inoculated on Blood agar, MacConkey agar and chocolate agar. Different biochemical tests were used to identify the Micro-organisms. RESULTS: Analysis of 173 patients' ages revealed that the patients were 18-67 years old, with a mean age of 28.6±3. Analysis of the gender-wise distribution of the 173 patients showed that 92(53.2%) were men and 81(46.8%) were women. Analysis of the distribution of micro-organisms among 173 patients revealed that 45(26%) and 36(20.8%) of them were staphylococcus aureus and Streptococcus. Staphylococcus epidermidis were 32 (18.5%). Pseudomonas aeruginosa were 34(19.7%) and E Coli were 26 (15.02%). The Gustilo classification was used to examine the distribution of fractures among 173 patients. Grade 1 consisted of 31, Grade II consisted of 48, Grade III consisted of 80, Grade IIIB consisted of 8, and Grade IIIC consisted of 6. CONCLUSION: This study concludes that both staphylococcus aureus were the frequent micro-organisms involved in open fracture infections.